Runtime Reconfiguration in Networked Embedded Systems Design and Testing Practices - Papp, Zoltan; Exarchakos, George (Internet of Things, Technology, Communications and Computing, 2016)
This book focuses on the design and testing of large-scale, distributed signal processing systems, with a special emphasis on systems architecture, tooling and best practices. Architecture modeling, model checking, model-based evaluation and model-based design optimization occupy central roles. Target systems with resource constraints on processing, communication or energy supply require non-trivial methodologies to model their non-functional requirements, such as timeliness, robustness, lifetime and "evolution" capacity. Besides the theoretical foundations of the methodology, an engineering process and toolchain are described. Real-world cases illustrate the theory and practice tested by the authors in the course of the European project ARTEMIS DEMANES. The book can be used as a "cookbook" for designers and practitioners working with complex embedded systems like sensor networks for the structural integrity monitoring of steel bridges, and distributed micro-climate control systemsfor greenhouses and smart homes.